Tagging effects on the mid-infrared spectrum of microsolvated protonated methane. Issue 6 (8th January 2018) - Esser, Alexander; Forbert, Harald; Marx, Dominik
Abstract : Although bare protonated methane is by now essentially understood at the level of intramolecular large-amplitude motion, scrambling dynamics and broadband vibrational spectra, the microsolvated species still offer plenty of challenges. Abstract : Although bare protonated methane is by now essentially understood at the level of intramolecular large-amplitude motion, scrambling dynamics and broadband vibrational spectra, the microsolvated species still offer plenty of challenges. One aspect is the effect of the attached solvent molecules on the infrared absorption spectra of microsolvated CH5 + complexes compared to the bare parent molecule. In this study we analyze, based on ab initio molecular dynamics simulations, protonated methane molecules that have been microsolvated with up to three hydrogen molecules, i.e. CH5 + ·(H2 ) n . In particular, upon introducing a novel multi-channel maximum entropy methodology described herein, we are able to decompose the infrared spectra of these weakly-bound complexes in the frequency window from 1000 to 4500 cm −1 into additive single mode contributions. Detailed comparisons to the bare CH5 + parent reveal that these perturbed modes encode distinct features that depend on the exact microsolvation pattern. Beyond the specific case, such understanding is relevant to assess tagging artifacts in vibrational spectra of parent molecules based on messenger predissociation action spectroscopy.